Partial versus radical nephrectomy in clinical T2 renal masses. (11th August 2021) - Klett, Dane E; Tsivian, Matvey; Packiam, Vignesh T; Lohse, Christine M; Ahmed, Mohamed E; Potretzke, Theodora A; Gopalakrishna, Ajay; Boorjian, Stephen A; Thompson, R Houston; Leibovich, Bradley C; Potretzke, Aaron M
Abstract : Objective: To report perioperative, renal functional and oncologic outcomes for patients undergoing partial or radical nephrectomy for cT2 renal masses. Methods: Retrospective review of patients who underwent partial ( n  = 72) or radical nephrectomy ( n  = 379) for cT2 renal masses from 2000 to 2016. After propensity adjustment using inverse probability weighting, the following were compared by surgery (partial or radical nephrectomy): complications, renal function measured by estimated glomerular filtration rate as continuous and as <60 mL/min/1.73 m 2 at 1 and 3 years postoperatively and overall, metastases‐free survival and cancer‐specific survival in patients with renal cell carcinoma. Results: After propensity adjustment, clinical and radiographic features were well‐balanced between groups. Overall and severe complications were more common for partial compared with radical nephrectomy, although not statistically significant (19 vs 13%, P  = 0.14 and 4 vs 2%, P  = 0.3, respectively). Estimated glomerular filtration rate change at 1 and 3 years was more pronounced in radical compared with partial nephrectomy (median −16 vs −5 and −14 vs −2, respectively, P  < 0.001). A greater proportion of radical nephrectomy patients had an estimated glomerular filtration rate <60 at 1 and 3 years (55 vs 17% and 48 vs 17%, respectively, P  < 0.01). In renal cell carcinoma patients, overall, metastases‐free and cancer‐specific survival were not significantly different between groups (median survivor follow up 7.1 years, interquartile range 3.6–11.4). Conclusions: Partial nephrectomy appears to be a relatively safe and a potentially effective treatment for cT2 renal masses, conferring better renal functional preservation compared with radical nephrectomy. These data support continued use of partial nephrectomy for renal masses >7 cm in appropriately selected patients.